Opting out from European Union legislation: the differentiation of secondary law. Issue 3 (9th March 2017) - Duttle, Thomas; Holzinger, Katharina; Malang, Thomas; Schäubli, Thomas; Schimmelfennig, Frank; Winzen, Thomas
ABSTRACT: Differentiated integration in the European Union (EU) has been primarily discussed and analysed at the treaty level, whereas lack of systematic data has hampered the examination of secondary-law or legislative differentiation. We present a new data set of differentiation in EU legislation from 1958 to 2012, a descriptive analysis and a comparison of the patterns of primary- and secondary-law differentiation across time, member states and policies. We find that differentiation facilitating the accession of new members and constitutional differentiation accommodating the opposition against the integration of core state powers drive both primary- and secondary-law differentiation. In addition, we find complementarity between differentiation in treaty law and secondary legislation depending on the availability and salience of differentiation opportunities.